A peptide translated from circPPP1R12A promotes the malignancy of non‐small cell lung cancer cells through AKT signaling pathway. Issue 10 (21st August 2022) - Zhao, Weijun; Xue, Yibo; Zhang, Yandan; Zhu, Yonggang; Chen, Zixuan; Zhao, Xiaodong
Abstract: Background: Recent literature have indicated that the malignancy of cancer cells is modulated by hsa_circ_0000423 (named circPPP1R12A) through the way of translating protein. Herein, we investigated the role and latent mechanisms of circPPP1R12A in Non‐Small Cell Lung Cancer (NSCLC). Methods: CircPPP1R12A expression was measured by qRT‐PCR. The malignancy of NSCLC was determined by CCK‐8, TUNEL assay, Wound healing, Transwell and Western blotting assays. The underlying mechanisms of circPPP1R12A were confirmed by Western blotting and qRT‐PCR assays. Results: CircPPP1R12A expression in NSCLC tissues was higher than that of neighboring normal tissues. CircPPP1R12A showed an upregulated expression in NSCLC cells. Upregulation of circPPP1R12A could promote the cell viability of NSCLC cells and reduce the apoptosis of NSCLC cells, while it could not promote cell invasion and migration. The reduction of cell viability and apoptosis was discovered in NSCLC cells with the silencing of circPPP1R12A, but circPPP1R12A knockdown does not inhibit cell invasion and migration. There was something interesting that circPPP1R12A encoding protein circPPP1R12A‐73aa was found in NSCLC cells. Mutations in circPPP1R12a‐73AA might disrupt the function of circPPP1ra‐73AA in A549 and H1299 cells. Next, we found that circPPP1R12A caused the increased growth of NSCLC cells by activating AKT signaling pathway. Conclusion: In summary, our study proved that NSCLC cell proliferation was promoted by circPPP1R12A‐73aa translated from circPPP1R12A through the AKT pathway, which could throw some light on the understanding of the mechanism of NSCLC. Abstract : CircPPP1R12A‐73aa translated from circPPP1R12A maintains the proliferation of NSCLC cells through the AKT signaling pathway.